Analysis of QTLs with genetic main effect, additive × additive epistatic effect and G×E interaction effect of rice transparency - SHEN Sheng-quan; ZHUANG Jie-yun; WANG Shu-zhen; SHU Qing-yao; XIA Ying-wu (浙江大学学报. 农业与生命科学版)
Recombinant inbred lines population derived from Zhenshan 97B/Miyang 46 (ZS97B/MY46) and its genetic linkage map were used to map the QTLs controlling rice transparency in different environments, Hainan and Hangzhou. A total of five QTLs with genetic main effects were detected on chromosomes 2, 6 (two QTLs), 8 and 10, which contributed to 19.15% of the total phenotypic variations. Among them, the additive effects of qTR2-2 came from the female parent while the other four (qTR6-1, qTR6-2, qTR8-2, qTR10) came from the male parent. The QTL qTR6-1 was also detected to have significant G×E interaction effects. In addition, two pairs of QTLs with additive × additive epistasis were detected, but they had no G×E interaction effect.